Reactive power sharing among distributed generators in a microgrid by using virtual current - Eder A. Molina-Viloria; John Edwin Candelo Becerra; Fredy Edimer Hoyos Velasco (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper presents a new autonomous effective power distribution control strategy for three-phase parallel inverters. The proposal uses a controller that can provide the system with accurate power sharing among distributed generators installed in the microgrid once some load variations are presented in the network. The methodology uses a virtual current loop introduced into the current controller of the inverter to optimize the output signal, which goes directly to the PWM. This virtual current is obtained by using a virtual impedance loop. Furthermore, a small-signal model of the system is used to check stability of the proposed control strategy, which was developed for island mode operation of the microgrid. Simulations were performed for a microgrid with two generators and a load with five households and implemented in MATLAB/Simulink software. The results show that the model provides a wide margin of stability and a rapid response when electrical loads change, thus fulfilling the reactive power sharing among generators. The proposed method shows a large margin of stability and a rapid transient response of the system.